A Study of Ursodeoxycholic Acid for Dissolution of Gallstones (TAJ: Journal of Teachers Association, 2018)
Background: Gallstone disease one of the major health problems and causes of morbidity in Bangladesh as well as worldwide. Ursodeoxycholic acid is a bile acid which is used for dissolving gallstones.Objectives: To observe dissolution of gallstones among the patients of gallstone disease by use of ursodeoxycholic acid. Methods: It was a cross-sectional observational study carried out in the Department of Medicine, Rajshahi Medical College Hospital, Rajshahi from July, 2014 to June, 2016. According to inclusion and exclusion criteria 12 people having gallstone disease were selected whose stone size were